T lymphocytes in infectious mononucleosis. II. Response in vitro to interleukin-2 and establishment of T cell lines. - Bishop, C J (1985)
The addition of 20% interleukin-2 (IL-2) significantly reduced the percentage of T lymphocytes dying in vitro after being isolated from the peripheral blood of acute infectious mononucleosis (IM) patients. Moreover, the immediate addition of 20% IL-2 to freshly isolated blood allowed IM T cell lines to be readily established from the peripheral blood of acute IM patients. Characterization of seven of these IM T cell lines showed them to be T3+, T11+, T4-, T9- and generally T10-. Over half of the lines characterized were T8+. It will now be possible to re-evaluate IM T cell effector functions as previous assays of IM T cell functions may have been influenced by the presence of rapid and extensive T cell death in vitro.